ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUH LOYALITAS PELANGGAN DAN DAMPAKNYA TERHADAP KEUNGGULAN BERSAING - Jatmiko, Robby (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2016)
In this research, the research model is proposed to analyze thecompetitive advantage through customer loyalty of BRITAMA BRI Branchof Kendal customers by testing the hypothesized factors influencing: brandreputation, customer satisfaction, and service quality. This study used asample of 105 customers BRITAMA BRI Kendal Branch. The data analysistool used is Structural Equation Modeling (SEM) in AMOS 4.01 program.The result of data analysis shows that the research model has good of fit andall research hypothesis can be proved. The conclusion taken is the brandreputation has a positive effect on customer loyalty, customer satisfaction has apositive effect on customer loyalty, service quality positively affects customerloyalty, service quality positively affects customer satisfaction, customer loyaltyhas a positive effect on competitive advantage and service quality positivelycompetitive advantage. Based on the results of the research can be taken thetheoretical implications that this study provides additional justification forsome antecedents that affect customer loyalty positively, namely brandreputation, customer satisfaction, and service quality. The influence of servicequality on customer satisfaction and the direct influence of service quality oncompetitive advantage. The managerial implications that can be given aresuggestions for BRITAMA BRI Management of Kendal Branch to pay moreattention to the customer satisfaction factor, as this is the most dominantfactor affecting customer loyalty. The limitation of this research is to test onlyone product from BRI only. Future research needs to develop research byadding product quality variables (Selnes, 1993) and testing the overall BRIproduct.